Competencias de las secretarias ejecutivas y su incidencia en el desarrollo administrativo de los departamentos ejecutivos de la universidad técnica de Babahoyo - Jaime Lamilla, Ariana Lucia (2021)
This research was conducted with the assistants of the human talent area of the Technical University of Babahoyo, whose main objective is to understand what are the competencies of the secretaries that affect the administrative development of the executive departments. The main negative aspect influencing secretaries is technology. As a first step, we sought to obtain different conceptualizations that later helped us to understand this topic in a significant way. The methodology used for this research was quantitative research, it is appropriate to achieve the objective since it focuses mainly on measurement and verification through data collection methods. Which are; the survey and statistical analysis. In addition we can focus on observable data such as body language, behavior or visual elements at the time of the survey. Then the application of the survey was carried out, which provided us with accurate information for us to be able to use or develop workshops, training with structured topics that can benefit the attendee, will also ensure customer satisfaction and also help in the progress of the institution. In addition, it was observed that this institution should have greater control over the development of the management using the various secretarial skills.